European integration from nation-states to member states - Bickerton, Christopher J. (Oxford Oxford University Press, 2012)
'European Integration' outlines in empirical detail the mysteries and paradoxes of European integration. It challenges the convention of studying individual aspects of EU policymaking in isolation from the wider whole and situates the EU within the broader conceptual universe of the changing nature of the state in Europe.
Includes bibliographical references and index.
Keywords: European Union countries -- Economic integration